A Holistic Model of English Lesson-Unit Assessment for Junior High School Students - Rochmawati, Desi (Indonesian Journal of English Language Studies (IJELS), 2015)
Assessment in the learning process is very important. It is useful to know whether the teaching and learning process succeed or not. It can help to identify the students‘achievement. An assessment is usually done by teachers and it covers the three aspects;knowledge, skills, and attitude (social and spiritual). In accordance with curriculum 2013, thisstudy develops the model of assessment which is simpler and integrated. Moreover, teachersright now have many things to do related with administration affairs and other portfolios.They do not want to be burdened with some kinds of evaluation or assessment forms whichwill take too much of their time. This study, therefore, is aimed at designing a holistic modelof assessment, which is designed for the unit lesson. The model is a holistic assessmentmodel. In the model, Core Competence 1 (CC1) and Core Competence 2 (CC2) are notindicated explicitly because they are integrated in Core Competence 3 (CC3) and CoreCompetence 4 (CC4). The data were collected by having group discussion and sharing aquestionnaire to the students in English Language Studies. The result of this study is aholistic model of assessment to assess Junior High School students‘ achievement in learningEnglish. This model of assessment is designed especially to assess students‘ achievement inevery unit lesson. The model is presented in a table with likert scale scoring of 1 to 4. Someexplanation is also needed in certain points. The assessment is conducted by the students,they do self-assessment and peer assessment. The teacher does portfolio assessment of thestudent‘s work. A Holistic Assessment for Junior High School is the appropriate formbecause in the model, a holistic approach has been implemented: the contents are not toocomplex but they already represent the whole competence.Keywords: assessment, knowledge, skill, attitude, holistic, Core Competence